PERBANDINGAN IDENTIFIKASI Toxoplasma gondii MENGGUNAKAN METODE POLYMERASE CHAIN REACTION (PCR) DAN METODE ENZYME LINKED FLUORESCENT ASSAY (ELFA) - Miftahul Mushlih; Alifia Nurfitriana; Kurnia Wahyu Ningsih; Nurul Azizah; Nia Lukita Arian (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2020)
Toxoplasmosis is an infectious disease that does not show specific symptoms. This study aimed to determine the differences results of T. gondii detection in human blood using the PCR (polymerase chain reaction) with the ELFA (Enzym Linked Fluorescent Assay) method. The research was done by descriptive exploratory methods. Samples taken from 9 West Sumatra Pramita Clinics Laboratory and 1 person came from Sidoarjo as a control. Data analyzes was conducted by a chi-square test with a 95% confidence level. In the ELFA method detects IgG Anti-Toxoplasma. Whereas the molecular test detects B1 gene target. The serological test was able to detect 9 patients of toxoplasmosis and 1 patient was negative/ control. The molecular test showed a specific band with 195 bp in length. The accuracy of the molecular test was 77% (T count (4.4) T table (3.84). Based on the results its can be concluded that there a difference in identification between the PCR method and the ELFA method.